Analytical and Numerical Methods for the Identification of Torsional Oscillations and Forcing in Internal Combustion Engines - Dario Santonocito; Sebastian Brusca (Engineering Proceedings, 2025)
Crankshafts, present in internal combustion engines, are mechanical parts subject to torsion and bending that vary over time and, if the forcing is close to one of the natural frequencies of the system, they can encounter problems of torsional oscillations. These vibrations can lead to maximum oscillation amplitudes, with consequent fatigue stresses that would compromise the resistance and correct functioning of the shaft. The aim of this work is to indicate a methodology for identifying the natural frequencies of the crankshaft and the decomposition of the torques, due to gases and inertia, to identify the different harmonics; in fact, if one of these harmonics is close to the natural frequency of the crankshaft, the system will go into resonance.